PENGEMBANGAN WEBSITE PADA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DENGAN APLIKASI CMS WORDPRESS - Teguh Aryanto; Rasimin Rasimin; Abdul Ghoni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The development of science, technology and art (science and technology) brings global changes, including in the world of education. This development demands quality human resources to create increasingly attractive media and educational materials. This development research aims to look at the effectiveness of website products with wordpress applications to improve learning outcomes of fourth grade MI students. Based on the feasibility level of the media with a score of 82.89 and the material with a score of 96.25 shows that the media is valid enough to be tested in the experimental group. The trial results showed a significant improvement in student learning outcomes in the Social Sciences sub-topic Uniqueness of the Place Where I Live. This type of research is Research Reseach Development and Development (R&D) with ADDIE model procedures performed. The feasibility level of the media and material is 55 with. Student learning value is measured by the Minimum completeness Criteria (KKM) 70, the student learning outcomes achieved indicate an increase in class average from 55.00 to 85.50 of students totaling 20. The data was obtained in the experimental phase of the experimental class with the pretest instrument and post test. The conclusion of the research is that the website learning media with wordpress application effectively improves the learning outcomes of fourth grade students of MI Sunan Pandanaran (MISPA), Sardonoharjo Ngaglik Sleman Temple on Social Studies sub theme theme of Regional Uniqueness in my place.